Perceived organisational support and perceived supervisory support as predictors of organisational commitment of Malaysian academics - Jais J.; Mohamad M. (American Scientific Publishers, 2023)
Recent years have seen a substantial expansion in academic research on organisational commitment, particularly focused on private sector. With the emerging challenges of privatisation of higher education, it is not obvious that these results also are applicable to academics. To explore this gap, this study analysed the role of perceived organisational support (POS) and perceived supervisory support (PSS) in developing academics commitment. Quantitative data from 220 academics across 6 universities in Malaysia is analysed using Pearsons correlation. Results showed a partial relationship between POS, PSS and organisational commitment, suggesting that managerial support play a critical role in enhancing academics commitment. Implications of these findings are discussed. 2017 American Scientific Publishers. All rights reserved.